UTILIZATION OF EUCALYPTUS GRANDIS LEAF WASTE IN THE PRODUCTION OF VCO BASED LIQUID SOAP - Desi Ardilla; Khairunnisa Rangkuti; M. Taufik (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Eucalyptus grandis  still not much used, especially the leaves. Besides being used as an industrial material, Eucalyptus is also used as a medicinal plant to cure infectious diseases, fever and rheumatism as well as being an antiseptic and can be applied in the form of bath soap. The purpose of this study was to determine the best combination of liquid body soap with the addition of eucalyptus leaf extract with various concentrations. The research method used was a laboratory experiment using a completely randomized design (CRD) method with the addition of eucalyptus oil A = 1% (w/w), B = 2% (w/w), C = 3% (w/w), D = 4% (w/w) and E = 5% in total VCO 80 oil, 40% KOH = 35 g, glycerin = 60 g, propyleneglycol = 35 g, three times the repetition. The parameters observed were the physicochemical properties of soap based on SNI Liquid Bath Soap 06-4085-1996 including free alkali content, namely A = 0.072%, B = 0.052%, C = 0.078%, D = 0.090$, E-), 104% , pH value, A= 8.36, B= 8.78, C= 8.80, D= 8.85 and E=8.94, Specific Gravity A= 1.008, B= 1.018, C= 1.009, D= 1.190, E = 1.014.